The annual reports of Local Research Ethics Committees - Foster, C. G. (Journal of medical ethics, 1995)
Each Local Research Ethics Committee (LREC) is expected to produce an annual report for its establishing authority. Reports from 145 LRECs were examined with regard to (a) whether the committees were working within the terms of the most recent guidelines from the Department of Health and (b) observations on the role of LRECs with particular reference to accountability. Most LRECs had produced a report, although their length varied greatly. Most reports showed how seriously the committee took its task. Most committees met many of the guidelines; for example, almost all had two or more lay-members. The guideline most frequently not met was that committees should have no more than 12 members. Many committees review very large numbers of projects (maximum 351). Approximately two-thirds provide details in the annual report of individual project titles, their author and the committee decision; all reports should contain this information. Although it may in fact happen more generally, only 23 per cent of the reports referred to any form of monitoring of the eventual outcome of the research. A significant issue to arise from the reports is the extent to which the framework for the operation of LRECs has been confused by the development of the purchaser-provider split. The paper concludes with suggestions for remedying the situation.